2015
DOI: 10.1186/s12971-015-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographic trends of tobacco-related cancers in Cyprus

Abstract: BackgroundCausal relationships have been previously established between smoking and various cancers. In Cyprus, 39 % of men and 14 % of women reported daily smoking in 2008. The objective of this study was to compare the incidence of tobacco-related cancers to all other cancers by district and rural–urban classification to understand the impact of tobacco in Cyprus.MethodsData on lung, urinary bladder, oral, pharyngeal, head/neck, and laryngeal cancers were obtained from the Cyprus Cancer Registry (1998–2008).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Also, among our main findings was that age proved to be another significant risk factor for lung cancer development, as larger proportions of lung cancer incidence were observed among patients aged ≥50 years, in accordance with the literature 32,33 . In addition, as the vast majority of patients included in the present study were permanent residents of urban or semi-urban municipalities, occupational or environmental factors might have hidden effects on lung cancer development, as highlighted in other studies 14,34,35 . Furthermore, it has been reported that different smoking habits between rural and urban regions result in geographical inequalities in lung cancer incidence distribution 34 .…”
Section: Discussionmentioning
confidence: 69%
“…Also, among our main findings was that age proved to be another significant risk factor for lung cancer development, as larger proportions of lung cancer incidence were observed among patients aged ≥50 years, in accordance with the literature 32,33 . In addition, as the vast majority of patients included in the present study were permanent residents of urban or semi-urban municipalities, occupational or environmental factors might have hidden effects on lung cancer development, as highlighted in other studies 14,34,35 . Furthermore, it has been reported that different smoking habits between rural and urban regions result in geographical inequalities in lung cancer incidence distribution 34 .…”
Section: Discussionmentioning
confidence: 69%
“…In addition, place of residence seems to be a core component of lung cancer incidence and mortality trends, as highlighted by the current and other studies [34, 35]. It is obvious that a wide range of factors, such as demographic, occupational and environmental, are linked with rurality.…”
Section: Discussionmentioning
confidence: 77%
“…It is obvious that a wide range of factors, such as demographic, occupational and environmental, are linked with rurality. These factors may have hidden effects on lung cancer epidemics; such effects are more severe in geographical regions where prevalence of smoking is higher (e.g., urban or semi-urban municipalities) [35]. Geographical inequalities in lung cancer incidence distribution may be observed due to the different smoking habits between rural and urban regions.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Cyprus reported TRCs in Cyprus and compared AARs in rural and urban districts and also compared the data with the data of many other European countries. [ 12 ] A study on upper gastrointestinal cancers clustering and geographical variation in North China found a difference in various geographical areas is due to regional differences. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%